Analisis Kelayakan Finansial Kopi Bubuk Arabika dalam Kemasan Drip Bag (Studi Kasus Kelompok Tani Berdikari, Kabupaten Sumedang) - Lukito Hasta Pratopo; Ahmad Thoriq; Drupadi Ciptaningtyas (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Arabica coffee powder in drip bag packaging is a new product innovation created to fulfill consumer desires and increase product sales. This study aims to analyze the financial feasibility of arabica coffee powder in drip bag packaging. Primary data was collected through direct observation and interviews while secondary data was collected from published scientific references. Financial analysis is carried out to obtain information on Production Costs (BP), Cost of Production (HPP), Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR) and Payback Period (PBP). The results showed that natural processing of coffee beans with a production capacity of 84,143 drip bag packages per month and raw materials for green coffee beans with a moisture content of 30% - 40% resulted in a production cost of IDR 143,603,885.74 per month and HPP of IDR 1 .706.67 per drip bag. At a product selling price of IDR 2,500.00 per drip bag packaging, an NPV value of IDR 4,118,480,686 was obtained, a BCR of 1.44, an IRR of 36.00% and PBP occurred in the 3rd month.